2001
DOI: 10.1177/1525822x0101300402
|View full text |Cite
|
Sign up to set email alerts
|

A Case in Case Study Methodology

Abstract: The purpose of this article is to provide a comprehensive view of the case study process from the researcher's perspective, emphasizing methodological considerations. As opposed to other qualitative or quantitative research strategies, such as grounded theory or surveys, there are virtually no specific requirements guiding case research. This is both the strength and the weakness of this approach. It is a strength because it allows tailoring the design and data collection procedures to the research questions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
268
0
42

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 422 publications
(311 citation statements)
references
References 15 publications
1
268
0
42
Order By: Relevance
“…To compensate for this and increase generalizability, the findings in this paper are compared with previously developed theory. This has been referred to as analytical generalizability (Meyer, 2001;Yin, 2009) and is recommended for single case studies. The reasons and justifications for choosing this case study began with the selection of the supplier, and then the selection of the BMs.…”
Section: Methodsmentioning
confidence: 99%
“…To compensate for this and increase generalizability, the findings in this paper are compared with previously developed theory. This has been referred to as analytical generalizability (Meyer, 2001;Yin, 2009) and is recommended for single case studies. The reasons and justifications for choosing this case study began with the selection of the supplier, and then the selection of the BMs.…”
Section: Methodsmentioning
confidence: 99%
“…The case study is viewed as a suitable research strategy due to its easy approach as "when" and "how" questions can be created with less control over the event and when the focus is on a contemporary phenomenon within some real-life context (Yin, 2003). Meyer (2001) emphasized that the case study approach gives more room to tailor, the research design, and data collections procedures to the identified research questions. Through the comprehensive comments and views obtained from the interviewees, the case study approach would be able to provide deep understanding on how effective employees' engagement is in corporate responsibility programs.…”
Section: Research Design and Methodologymentioning
confidence: 99%
“…Further, it could overcome the problem of generalizing from a single case study and provide more in-depth analysis of complex organizational phenomena than questionnaire surveys (Larsson, 1993). Multiple cases increase the external validity and act as help guard against observer biases (Meyer, 2001). Regarding application of multiple case methods, Yin (1981) has described the design of case study research.…”
Section: [Insert Figure 1]mentioning
confidence: 99%
“…In the recent past, scholars have used qualitative methods such as case study research, historical research and content analysis, just to mention a few (Meyer, 2001;Stake, 1995, Yin, 1994, 2003. For instance, Larsson and Lubatkin (2001) used multi-case-survey to study acculturation in M&A deals.…”
Section: Introductionmentioning
confidence: 99%